Cyclic Production Scheduling with Remanufacturing - Aminipour, Armin (2015)
A Master of Science thesis in Engineering Systems Management by Armin Aminipour entitled, "Cyclic Production Scheduling with Remanufacturing," submitted in June 2015. Thesis advisor is Dr. Zied Bahroun and thesis co-advisor is Dr. Moncer Hariga. Soft and hard copy available.